NLP TOKEN MATCHING ON DATABASE USING BINARY SEARCH - Aggarwal, Ekta; Nair, Shreeja (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Natural Language Processing (NLP) is an area of research and application that explores how computers can be used to understand and manipulate natural language text or speech to do useful things. The paper deals with the concept of database where by the data resources data can be fetched and accessed accordingly with reduced time complexity. The retrieval techniques are pointed out based on the ideas of binary search. A natural language interface refers to words in its own dictionary as well as to the words in the standard dictionary, in order to interpret a query. The main contribution of this investigation is addressing the problem of improving the accuracy of the query translation process by using the information provided by the database schema.Â Â 